Musical Bridges to Memory (MBM): Exploring the effects of a dyadic music‐based group intervention on social engagement and neuropsychiatric symptoms in persons with dementia: Dementia care research (research projects; nonpharmacological)/Therapeutic strategies and interventions. (7th December 2020) - Schafer, Rhiana; Karstens, Aimee J; Hospelhorn, Emma; Wolfe, Jeffrey; Ziemba, Amanda; Wise, Peggy; Crown, Rickie; Rook, Jenni; Bonakdarpour, Borna
Abstract: Background: Music‐based interventions can reduce the severity of neuropsychiatric symptoms in persons with dementia (PWD), and in turn reduce the need for pharmacological interventions (e.g., psychotropic). However, few intervention trials have used a dyadic group approach. We determine the efficacy of a dyadic music‐based intervention on PWD neuropsychiatric symptoms and social engagement. Musical Bridges to Memory (MBM) uses both perceptive and expressive forms of music‐based intervention, administered in a dyadic group setting, to mediate PWD neuropsychiatric symptoms and improve social interaction between dyads (PWDs and their caregivers). Method: Thirty‐one dyads were recruited from memory care facilities; twenty received the MBM intervention, ten were controls. Groups were comparable in age and level of education. All were assessed at baseline and post‐intervention. Caregiver‐reported PWD behavioral symptoms were assessed using the Neuropsychiatric Inventory (NPI). The Verbal and Nonverbal Interaction Scale (VNVIS) was used to rate PWDs social interactions (10min video recordings of dyads) on sociable, unsociable, verbal and nonverbal behaviors. The 12‐week intervention included weekly sessions, which consisted of caregiver training(30m), live concerts(45m), and breakout groups(30m). Music was chosen based on PWDs' assessed preferences. Result: Sociable interactions (e.g. positive affect, eye‐contact, apparent interest/focus), significantly increased ( p =0.044) in the MBM intervention group as compared to controls. Caregivers reported a decrease in severity of PWD neuropsychiatric symptoms ( p =0.089, indicating a trend) and symptom‐related distress in caregivers ( p =0.005) decreased significantly. Analyses controlled for sex and global cognition (Mini Mental State Exam) score at baseline. Conclusion: Our preliminary results indicate that a dyadic music‐based group intervention approach administered in a memory care facility is effective at improving PWD social engagement, mitigating PWD behavioral symptoms, and reducing associated caregiver distress. These results complement previous literature, highlighting music‐based interventions as a non‐pharmacological approach to managing neuropsychiatric interventions in PWD. In addition, our use of a dyadic group‐based approach and our reported increase in sociable engagement highlights the benefits of including caregiver participation in music‐based interventions. Future work will examine a larger cohort and directly examine caregiver burden.